Economic and socio-cultural transformation of communities through the implementation of village forest policy in Sigi regency - Dasril, Muhamad; Gani, A. Juli Andi; Domai, Tjahjanulin; Mardiyono, Mardiyono (Edelweiss Applied Science and Technology, 2025)
This study explores the socio-economic and cultural transformation of forest-adjacent communities in Namo and Lonca Villages, Sigi Regency, Central Sulawesi, through the implementation of Indonesia’s village forest (Hutan Desa) policy. Anchored in the Regulation of the Minister of Forestry P.89/Menhut-II/2014, the policy grants legal forest management rights to communities, aiming to improve livelihoods while promoting sustainable forest use. Using a qualitative approach, the research reveals that village forest management has generated tangible economic benefits—such as increased household income and employment opportunities—mainly through the development of Non-Timber Forest Products (NTFPs) like rattan, bamboo, and forest honey. Socially and culturally, the policy has revived traditional wisdom and empowered local governance structures (LPHDs), though limitations persist due to institutional capacity and government support gaps. The study concludes that village forests hold strong potential as a model for inclusive, sustainable development, but success hinges on capacity building, inter-institutional collaboration, and continuous policy support.